FUEL CELL: FEASIBILITY ANALYSIS OF ITS APPLICATION IN AUTOMOBILES - Gontijo, R. M.; Silva, L. M.; Pereira, A. R. (Revista de Engenharia Térmica, 2018)
The need to reduce the emission of harmful gases into human life, together with the dependence on oil as a primary source of fuel for internal combustion engines (ICE), are part of the current global scenario. This scenario opens space for fuel cells (FC), technology that generates electricity as the main product of oxide-reduction reactions between Hydrogen and Oxygen. An efficient and clean alternative that appears as a possibility for the substitution of ICE. The present article proposes a model of FC and compares it technically with a conventional ICE, in order to prove the efficiency, performance and environmental impact feasibility of the use of this technology in commercial vehicles.